Post-Exercise Hypotension and Reduced Cardiac Baroreflex after Half-Marathon Run: In Men, but Not in Women; International Journal of Environmental Research and Public Health; Vol. 17, iss. 17 - Mourot L. Laurent; Fornasiero A. Alessandro; Rakobowchuk M. Mark; Isacco L. Laurie; Brighenti A. Alfredo; Stella F. Federico; Zignoli A. Andrea; Pellegrini B. Barbara; Tarperi C. Cantor; Schena F. Federico (2020, 2020)
Title screen